SISTEM DAN PROSEDUR DANA KAS KECIL PADA KOPERASI BALAI BESAR PELATIHAN KESEHATAN (BBPK) JAKARTA - Darry Septy Fadhila, - (2017)
This final project aims to find out how the petty cash accounting system applied to Koperasi BBPK Jakarta, whether the system is in accordance with Standard Operating Procedures (SOP) applied to the company, as well as to know the system and procedures used by the Cooperative BBPK Jakarta. The method used is the method imprest system System and procedures of petty cash funds in the Cooperative BBPK Jakarta with the method of imprest system is good enough, evidenced by the authorization of each related function authorized in the relevant documents, the provision of printed serial number and separation between related functions . Although there is still something to be fixed, the document is only made in duplicate so not all parts have a copy document. At the time of the petty cash disbursement request there is no comparison with supporting documents such as proof of expenditure